Development of Questionnaires for Assessing Anxiety, Sleep Quality, and Quality of Life in the Elderly for Nursing Practice - Praptomo, Agus Dodi; Winta, Mulya Virgonita I; Pratiwi, Margaretha Maria Shinta (International Journal of Nursing Information, 2024)
The elderly face complex and interrelated health challenges, including anxiety, sleep disturbances, and decreased quality of life, which can affect their physical and psychological well-being. In nursing, screening using valid and reliable questionnaires can help nurses identify mental health problems early, prevent complications, and provide appropriate interventions. Therefore, assessment scales such as the Elderly Anxiety Questionnaire (EAQ), Elderly Sleep Quality Questionnaire (ESQQ), and Elderly Quality of Life Questionnaire (EQLQ) were developed to assess anxiety, sleep quality, and quality of life in the elderly according to current conditions and needs. This study aims to develop and validate the EAQ, ESQQ, and EQLQ as initial screening tools for clinical and community practice nurses. The method used a qualitative approach; questionnaires were distributed to 60 elderly participants selected based on inclusion and exclusion criteria, followed by statistical validity and reliability tests. The results showed that the r-count value for the three questionnaires was more significant than the r-table (0.254), indicating good item validity. The reliability test using Cronbach's alpha also showed that the three questionnaires had high reliability. In conclusion, EAQ, ESQQ, and EQLQ are practical tools for detecting the mental condition of the elderly and supporting the role of nurses in providing comprehensive care. This study contributes significantly to nursing practice by providing tools for initial screening, data collection, and analysis to improve the quality of care for the elderly. Further research with a larger sample size is recommended to strengthen these findings.